Sentidos do consumo e fronteiras simbólicas: Uma etnografia entre grupos de baixa renda em um município da Grande São Paulo, Brasil - de castro, Ana Lúcia [UNESP] (OpenEdition, 2016)
The article presents a reflection about the impact of having access to consumption in the sensibilities and daily practices of a new group of consumers, recently constituted in Brazil. It attempts to understand to what extent consumption assumes different meanings within this low-income class, at times distant from seeking distinction and / or emulation as pointed out, repeatedly, by sociological explanations. Taking the symbolic dimension of consumption as an analytical key and focusing on the circulation of goods and brands – associated with a middle-class universe, its uses and new meanings –, the ethnography aims to understand the concept of middle-class expressed in the perceptions of individuals belonging to lower classes residing in a suburb of São Paulo. This leads to a reflection on how the inclusion of this group in the consumer market would allow these new consumers to build, or not, a sense of belonging to an alleged “middle-class” or establishing symbolic boundaries, both internally and externally to the group.
Senses of consumption and symbolic boundaries: An ethnography of low-income groups in a township of the greater São Paulo, Brazil
Keywords: Consumption; Identity; Social distinction; Symbolic re-signification; Urban groups